"Why wasn't I doing this before?": Changed school social work practice in response to the COVID-19 pandemic. (May 2023) - Phillippo, Kate; Lucio, Robert; Shayman, Emily; Kelly, Michael
The American education system has been significantly disrupted by the COVID-19 pandemic, which led schools to shut down and convert to remote learning environments in spring 2020. However, long before these school closures, school social workers (SSWs) have faced significant practice dilemmas, as they have encountered obstacles to their engagement in best practices. While initial pandemic school closures presented SSWs with a range of uncertain situations, they also provided the possibility to respond to practice demands in different and dynamic ways. This article explores the pandemic's impact upon SSWs' practice, and how SSWs responded in turn as they quickly adapted their practice during this widespread, ongoing crisis. Informed by crisis theory, previous analyses of SSW practice trends and dilemmas, and a review of traditional social work values and ethics, we conducted three focus groups in July 2020 with SSWs during the pandemic's early months. From these interviews, we learned that participants' work was disrupted by dramatic shifts in school and community settings, as well as changes in support needs within their respective school communities. Those disruptions gave way to substantial shifts in practice, which reflect a more prominent role for systemic practice and for traditional social work values in SSW decision-making. These findings offer implications for post-pandemic practice, and practice in other host settings.